Drugs used in wheeze associated respiratory infection among children in tertiary care teaching hospital - Paramasivamsasanger, Kamalavarshini; Arumugam, Bhakiyanathan; Sundararajan, Parimalakrishnan; Kumar, Praveen Kumar Ravi (International Journal of Basic & Clinical Pharmacology, 2020)
Background: This study was done to study the drugs used in wheeze associated lower respiratory infected paediatric patients in tertiary care teaching hospital. Methods: Sample size was calculated as 78 and patients were selected based on the inclusion and exclusion criteria. The study was a prospective observational study and conducted in Department of Pediatrics, Rajah Muthiah Medical College and Hospital (RMMCH), Annamalai University. Results: Our study shows that male children (63%) are affected with more than female children (37%). The most frequently prescribed drugs are antibiotics (96%), antipyretics (63%), expectorants and antitussives (54%) followed by beta adrenergic agonist (46%), beta adrenergic agonist with anticholinergic combination (14%) corticosteroids (18%). Our study also shows wheeze associated lower respiratory infection (WALRI) in children were significantly associated with bacterial infections (72%). Conclusions: Our study concluded that antibiotics and antipyretics are the most commonly prescribed drugs for WALRI followed by expectorants and antitussives, beta adrenergic agonist, corticosteroids, beta adrenergic agonist with anticholinergic combination. Most of the treatment strategies are adopted from Standard Treatment Guidelines (STG) and World Health Organisation (WHO). The average number of prescribed drugs per encounter was more than that of WHO standards. The percentage of encounters in which an antibiotics and injections was higher than the ideal WHO standards it leads to anti-microbial resistance and costly forms of drug therapy.